OBSESSIVE-COMPULSIVE PARTICULARITIES BEFORE AND AFTER REMISSION OF ACUTE PHASE EPISODES OF SCHIZOPHRENIA - Dragoi, Ana Miruna; Enache, Angela; Vlaicu, Ilinca; Trifu, Amelia Damiana (International Journal of Research -GRANTHAALAYAH, 2019)
Motivation/Background: We aim at presenting a case that would circumscribe to the concept of schizo-obsessive disorder, in which the onset at the end of adolescence was with OC phenomenology, the negative symptoms appearing subsequently, while the productive perceptual and ideational area (auditory hallucinations and pseudohallucinations, next to the reference delusional ideation and Kandinsky Clerambault syndrome) developed at about one year and a half after social insulation. To be noticed that in residual phases, OC phenomenology acquires other connotations than those prior to schizophrenia onset, the patient never acquiring again a total insight on the disorder. Method: Computed EEG, psychiatric interview, psychodynamic interview, psychiatric and psychological monitoring of daily evolution under treatment, life map, heteroanamnesis, psychological tests, psychodynamic interpretations. Results: According to Poyurovsky’s guide, the case circumscribes to the diagnostic of schizo-obsessive disorder. When obsessions and compulsions were related to the content of delusional ideas and hallucinations, other typical rituals of obsessive-compulsive disorders appeared too, the patient considered sometimes irrational and excessive. Conclusions: Social degradation of the patient is dictated mainly by the negative dimension of schizophrenia, secondly by energy consumption in fulfilling the rituals and compulsions and last but not least by the mood change in depressive sense.